Ethnic disparities in prevalence of chronic non-communicable diseases and its multimorbidity among older adults in rural southwest China - Ying-rong Du; Lan Liu; Yi Zhao; Jing-jing Huang; Allison Rabkin Golden; Le Cai (BMC Public Health, 2023)
Abstract Background As the population ages, chronic non-communicable diseases (NCDs) multimorbidity has emerged as a major public health issue globally. This study examines ethnic disparities in prevalence of NCDs and its multimorbidity among rural southwest Chinese older adults. Methods A cross-sectional survey was conducted in rural southwest population aged ≥ 60 years consisting of 5,642 consenting participants of Han and three ethnic minority groups (Dai, Ha Ni, and Bai). Information about participants’ demographic characteristics and lifestyle behaviors was obtained using a standard questionnaire. Anthropometric measurements including height, weight, and waist circumference, fasting blood sugar and blood pressure measurement, as well as post-bronchodilator spirometry test were recorded for each participant. Results The age-standardized prevalence of five common chronic NCDs– hypertension, diabetes, coronary heart disease (CHD), stroke, chronic obstructive pulmonary disease (COPD) – and its multimorbidity was 72.8%, 15.9%, 4.0%, 10.0%, 9.8%, and 27.6%, respectively. Bai participants had both the highest overall and sex-specific prevalence rates of hypertension, diabetes, stroke, and COPD, whereas Han participants had the highest rates of CHD (P < 0.01). The results of multivariate logistic regression analysis indicated that female and older participants had a higher probability of chronic NCDs multimorbidity than their counterparts (P < 0.01). Bai ethnic minority participants were more likely to have NCDs multimorbidity while Ha Ni and Dai ethnic minority participants were less likely to have NCD multimorbidity relative to the Han participants (P < 0.05). Older adults with a higher level of education and family history of chronic NCDs, and who were also current smokers, current drinkers, obese, centrally obese, and physically inactive had a greater probability of developing chronic NCDs multimorbidity (P < 0.01). Conclusions Ethnicity and individual demographic and lifestyle factors significantly impact prevalence of chronic NCDs multimorbidity. Future chronic NCDs prevention and control strategies must be tailored to address ethnicity, and culturally tailored lifestyle interventions may reduce the prevalence of chronic NCDs multimorbidity in rural southwest China.